T.S. Eliot’s Impersonal Theory in Arbind Kr. Choudhary’s PoetryLove (International Journal of Psychosocial Rehabilitation, 2020)
This paper will explore Arbind Arbind Choudhary’s poetry Love (2011) from the perspective of T.S. Eliot’s ideas on Tradition and the Individual Talent (1919). It will focus on Choudhary’s impersonal expression of love, where he blends both tradition and modernity to juxtapose the universal idea of love. In the poetry Love (2011), Choudhary blends both eastern and western mythology along with the fusion of past and present situations of love. Love is a divine inspiration that gives eternal bliss to all human beings. It overcomes the ravages of time and space. Spiritual love is better than sensuous love or materialistic love. In modern times, love gives disastrous consequences that destroy the sanctity of real love. To show the universal quality of love, the poet juxtaposes the love of the ancient gods and goddesses from India, Greece, and Rome. The loves of Diana, Venus, Adonis, Apollo, Shakuntala, Laila, Majnu, Ram, and Sita are immortal loves who all sacrifice for the true love that inspires the love seekers. True love builds a grove that stirs the passion among different lovers. The beauty of nature guides the true lovers, and the images of nature, like the moon, sun, starlit night, and spring season, give impetus to the lovers. Love rejects materialistic ideas on abortion, lesbianism, and philander which degrades a true relation among the lovers.